1994
DOI: 10.1182/blood.v83.6.1603.bloodjournal8361603
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of mutations in the ras proto-oncogenes in de novo acute myeloid leukemia

Abstract: Mutations of the N- and K-ras genes are the most frequent genetic aberrations in acute myeloid leukemia (AML) and their detection in preleukemic conditions such as the myelodysplastic syndrome (MDS) suggests a role in the earliest phases of leukemogenesis. Despite these observations, little is known about the clinical importance of ras mutations in AML. We studied the clinical impact of ras mutations in 99 patients with de novo AML. All patients were treated in two prospective multicenter trials. The polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(57 citation statements)
references
References 21 publications
6
47
1
3
Order By: Relevance
“…However, even though EO is capable of producing such effects, gene mutations have not been considered to be the initiating events for the chemically mediated leukemias in humans. While specific oncogene mutations (e.g., in N-ras and K-ras (Neubauer et al, 1994)) have been reported in a proportion of de novo leukemias, the chromosome aberrations described above are the characteristic changes found in the chemically induced leukemias (USEPA, 1997b;Levine & Bloomfield, 1992;Yunis et al, 1989).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…However, even though EO is capable of producing such effects, gene mutations have not been considered to be the initiating events for the chemically mediated leukemias in humans. While specific oncogene mutations (e.g., in N-ras and K-ras (Neubauer et al, 1994)) have been reported in a proportion of de novo leukemias, the chromosome aberrations described above are the characteristic changes found in the chemically induced leukemias (USEPA, 1997b;Levine & Bloomfield, 1992;Yunis et al, 1989).…”
Section: Mode Of Actionmentioning
confidence: 99%
“…[1][2][3] They are present overall in approximately 40% of all malignancies, and noted in up to 90% of pancreatic adenocarcinoma, 30% of non-small cell lung cancer, and approximately one-third of colorectal cancers. 1,2 Several series have reported RAS mutations in 10% to 25% of cases of acute myeloid leukemia (AML) [4][5][6][7][8][9][10][11][12][13][14] and 7% to 48% of cases of myelodysplastic syndrome. [15][16][17] N-RAS, K-RAS, and H-RAS are the most common isoforms of RAS involved in human cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] RAS proteins are a crucial component of the signaling transduction pathways and result in the control of cellular proliferation, differentiation, and cell death. [11][12][13][14][15][16] Under normal conditions, RAS activation is triggered by the binding of growth factors to plasma membrane receptors with tyrosine kinase activity. 14 The activation of these pathways is dependent on farnesylation.…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%
“…In MDS, N-RAS mutations have been detected in 10-40% of cases. 16 These mutations have been associated with poor prognosis, higher incidence of transformation to AML, and shorter survival. Patients with abnormal karyotypes and N-RAS mutations have the highest likelihood of transformation.…”
Section: Farnesyl Transferase Inhibitorsmentioning
confidence: 99%